Psychology of pandemics and fear of epidemic - Uddin, M. Naveed; Uddin, Mohsin (International Journal Of Community Medicine And Public Health, 2021)
Infectious outbreaks have stirred the psychological health and mental wellbeing of individuals on a global basis. It is evident from the 1918 influenza in addition to the current COVID-19. Psychological factors are significant for comprehension and overseeing cultural issues related with pandemics, like the spreading of extreme dread, anxiety, and xenophobia that happen when individuals are compromised with infection. The research aims to identify how the COVID-19 pandemic has affected individual’s psychological wellbeing and how the psychodynamic approach can resolve such an issue. Developing a sense of detachment from oneself and the growing fear of being infected significantly affects an individual psychological wellbeing. This analysis concentrates predominantly on applying the psychodynamic approach to ascertain individual’s psychological threats during the COVID-19 crisis. This research focuses on revealing the variations generated from the psyche of individuals due to the COVID-19. It also aims to highlight the impact that COVID-19 have created on the mental health of individual beings. Moreover, the pandemic consequence on the individual’s overall lifestyle has discussed in the study.